Body Temperature Regulation During Heat Stress in the Pregnant Rat - Wilson, Nancy E. (My University, 1974)
Body temperature regulation at high ambient temperatures was compared in pregnant and non-pregnant female albino rats. At an ambient temperature of 40°C, pregnant rats maintained lower body temperatures than non-pregnant rats without added expenditure of moisture for evaporative cooling. This was surprising because of the increased heat load on the pregnant animal resulting from a large weight gain and increased food intake. The maintenance of lower body temperatures in the heat by pregnant rats was possible because (1) pregnant rats produce less heat; i.e. consume less oxygen during exposure to 40°C than do non-pregnant rats and thus need to dissipate less heat; and (2) pregnant rats have a lower body temperature threshold for increased submaxillary salivary gland output in the heat, which makes more water for evaporative cooling available to them at lower body temperatures.
The maintenance of lower body temperatures in the heat by pregnant rats suggests that pregnant rats have a need or a preference for lower body temperatures in the heat. The change in body temperature regulation during pregnancy is likely related to physiological and anatomical changes in the body which accompany pregnancy. Alterations in body temperature regulation to meet the changed physiological state of pregnancy provide another example of the body's remarkable ability to maintain homeostasis.
Keywords: body temperature, regualtion, heat stress, pregnant rat